NEUROPROTECTIVE EFFECT OF ADSCs-CM ON MPP+-INDUCED SH-SY5Y CELLS AND ITS MECHANISM OF ACTION - XIAO Huanhuan, YIN Kan, XIAO Yu, ZHANG Zheng, HOU Lin (精准医学杂志, 2023)
Objective To investigate the neuroprotective effect of human adipose-derived mesenchymal stem cells-conditioned medium (ADSCs-CM) on 1-methyl-4-phenylpyridine (MPP+)-induced SH-SY5Y cells and the underlying mechanism. Methods SH-SY5Y cells were divided into three groups for 24 h culture: control group (basic culture medium), PD group (1.0 mmol/L MPP++ basic culture medium), and CM group (1.0 mmol/L MPP+ + ADSCs-CM). The content of reactive oxygen species (ROS) in SH-SY5Y cells was determined using a ROS assay kit. The total amount of adenosine triphosphate (ATP) in SH-SY5Y cells was measured using an ATP assay kit. The activity of mitochondrial complex Ⅰ (CⅠ) in SH-SY5Y cells was determined using a mitochondrial C Ⅰ activity assay kit. The autophagy rate of SH-SY5Y cells was observed by the monodansylcadave-rine fluorescence method. Western blot was used to measure the expression of mitochondrial autophagy-related proteins (P62 and LC3) in SH-SY5Y cells. Results Compared with the control and CM groups, the PD group showed significant differences in ROS content, total ATP amount, mitochondrial C Ⅰ activity, autophagy rate, and the relative expression levels of P62 and LC3 Ⅱ/Ⅰ proteins in SH-SY5Y cells (tLSD=3.23-12.61,P<0.05). Conclusion ADSCs-CM can improve MPP+-induced mitochond-rial dysfunction in SH-SY5Y cells, possibly through influencing the expression of autophagy-related proteins P62 and LC3.